Bat 6 - Wolff, Virginia Euwer (New York : Scholastic Press, 1998)
In a small town, post-World War Oregon, twenty-one sixth- grade girls recount the story of an annual softball game, during which one girl's bigotry comes to the surface.
930
Accelerated Reader AR
Keywords: Softball -- Fiction; City and town life -- Fiction; World War, 1939-1945 -- United States -- Fiction